PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI KELAS III SD NEGERI 012 KAMPAR TIMUR - Suyatmi, Chatarina; Syahrilfuddin, Syahrilfuddin; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to increase the students’ mathematics learning class III Elementary School 012 East Kampar by implementing cooperative learning model STAD. The background of this research is the low result of learning mathematics, seen from a value of 20 student do not reach KKM 12 student (60%) and reach KKM 8 student (40%) with an average value of 56. The minimum completeness criteria (KKM) is 61.The method of research is classroom action research, conducted in two cycles with phases including planning, action, observation, reflection. Data collection techniques are observation techniques, test, and documentation. Data collector uses observation sheets and test learning outcomes. Data were analyzed using analysis of the activities of teachers and students, as well as analysis of students learning outcomes. At the first meeting of the first cycle of teacher activity percentage 62,59% with a good category, the second meeting increased to 75,00% with a good category. At the first meeting of the second cycle percentage increased to 87,50% with verry good category, the second meeting increased to 100,00% with a verry good category. Activities of students has increased. In the fisrt cycle of the percentage in the fisrt meeting 64,38% with good category, the second meeting increased to70,70% with good category. At the first meeting of the second cycle increased to 88,55% with verry good category, the second meeting increased to 99,00% with verry good category. The average result of study prior to the application of the model is 56,00, rising to 71,00 in first cycle, and the second cycle increased to 98,00. The result showed that the application of cooperative learning model STAD can improve students’ mathematics learning outcomes.Key Word: Mathematics Learning Outcomes, Cooperative Learning Model STAD